THEORETICAL BASIS OF THE SELF-DEVELOPMENTOF THE SOCIO-ECONOMIC SYSTEM (REGION) - TOPALOVA, Iryna (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article analyzes the theoretical basis of the self-development of the region as a socio-economic system based on the use of its resource potential. The purpose of the article is the theoretical substantiation of self-development of regions as a priority vector of socio-economic development of Ukraine. This goal made it possible to form the following tasks: - to form a conceptual vision of the self-development of the region on the basis of the formation of resource potential (components of resource potential: reproductive and infrastructural; socio-economic; natural-resource; innovative and information and communication; components of the economic system: competitive advantages, regional and interregional connections, decentralization, regional and local authorities; the main goal is to obtain a result (satisfaction of the needs of the population); - carry out a content analysis of the term "self-development of the region"; - consider the components of the self-development process of the region (availability of potential, resources, production capacities; level of organization, management process, entrepreneurial skills, availability of qualified personnel, the opportunity to learn, building competences; production of material and immaterial goods; labor potential; formation of developed infrastructure; opportunities for innovative development); - to form meaningful components of the concept of "Self-development of regions": resource independence; system capabilities; development vectors; organizational changes; motivation; innovativeness; development; institutional and legal norms; clustering; determination of key capabilities of the region; - to determine tasks that can be solved in the region thanks to the provision of their self-development.